2023
DOI: 10.1039/d2ee03840d
|View full text |Cite
|
Sign up to set email alerts
|

A 5 V-class cobalt-free battery cathode with high loading enabled by dry coating

Abstract: Transitioning toward more sustainable materials and manufacturing methods will be critical to continue supporting the rapidly expanding market for lithium-ion batteries. Meanwhile, energy storage applications are demanding higher power and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 46 publications
0
46
0
Order By: Relevance
“…Thereby, the HRXPS analyses of the transition metal species confirm that the LiClO 4 -based electrolyte leads to a thinner CEI layer than the LiPF 6 -based electrolyte does. It is interesting to note that some very recent studies have indicated that the property of the CEI layers formed on DPEs and conventional electrodes is different, and DPEs indeed exhibit better electrochemical performance than conventional electrodes do. ,, …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thereby, the HRXPS analyses of the transition metal species confirm that the LiClO 4 -based electrolyte leads to a thinner CEI layer than the LiPF 6 -based electrolyte does. It is interesting to note that some very recent studies have indicated that the property of the CEI layers formed on DPEs and conventional electrodes is different, and DPEs indeed exhibit better electrochemical performance than conventional electrodes do. ,, …”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that some very recent studies have indicated that the property of the CEI layers formed on DPEs and conventional electrodes is different, and DPEs indeed exhibit better electrochemical performance than conventional electrodes do. 16,18,60 In view of the aforementioned analyses, the impact of the electrolytes on the high-loading PTFE-based DPEs can be ascribed to the following two aspects. (1) Electrolytes with different properties play a significant role in the electrochemical performance, especially ionic conductivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the large-scale manufacturing of solid-state batteries lacks a widely reported method [10,11]. Polymer binders are typically employed in the manufacturing process, which can be categorized as either slurry cast wet or solventfree dry processes [12][13][14]. The dominant electrode manufacturing technology is wet process which involves using organic solvent to create a slurry of active materials, conductive carbon and a soluble polymer binder [15,16].…”
Section: Introductionmentioning
confidence: 99%